Upper and lower urinary tract outcomes in adult myelomeningocele patients: a systematic review. - Paul W Veenboer; J L H Ruud Bosch; Floris W A van Asbeck; Laetitia M O de Kort (PLoS ONE)
Background The introduction of sophisticated treatment of bladder dysfunction and hydrocephalus allows the majority of SB patients to survive into adulthood. However, no systematic review on urological outcome in adult SB patients is available and no follow-up schemes exist. Objectives To systematically summarize the evidence on outcome of urinary tract functioning in adult SB patients. Methods A literature search in PubMed and Embase databases was done. Only papers published in the last 25 years describing patients with open SB with a mean age >18 years were included. We focused on finding differences in the treatment strategies, e.g., clean intermittent catheterization and antimuscarinic drugs versus early urinary diversion, with regard to long-term renal and bladder outcomes. Results A total of 13 articles and 5 meeting abstracts on urinary tract status of adult SB patients were found describing a total of 1564 patients with a mean age of 26.1 years (range 3-74 years, with a few patients <18 years). All were retrospective cohort studies with relatively small and heterogeneous samples with inconsistent reporting of outcome; this precluded the pooling of data and meta-analysis. Total continence was achieved in 449/1192 (37.7%; range 8-85%) patients. Neurological level of the lesion and hydrocephalus were associated with incontinence. Renal function was studied in 1128 adult patients. In 290/1128 (25.7%; range 3-81.8%) patients some degree of renal damage was found and end-stage renal disease was seen in 12/958 (1.3%) patients. Detrusor-sphincter dyssynergy and detrusor-overactivity acted as adverse prognostic factors for the development of renal damage. Conclusions These findings should outline follow-up schedules for SB patients, which do not yet exist. Since renal and bladder deterioration continues beyond adolescence, follow-up of these individuals is needed. We recommend standardization in reporting the outcome of urinary tract function in adult SB patients.